Pengaruh Pembelajaran Daring terhadap Efektivitas Belajar Mahasiswa Pendidikan Matematika di ITS NU Pasuruan - Alqodiri, Muhammad Dzawil Mukarrom; Millah, Rosyidatul; Julaikha, Siti (Jurnal Likhitaprajna, 2023)
This paper contains the results of an analysis of the effect of online learning on the learning effectiveness of mathematics education students at ITS NU Pasuruan. The method used in this research is a survey conducted online. Data sources were obtained from the results of using a research instrument in the form of a questionnaire. Respondents of this study were several students of mathematics education study program in semester 2 and 4. From the results of the analysis, several advantages were found as well as disadvantages in online learning.